Silver nanoparticles formulations for healing traumatic injuries in oral mucosa of rats - Curtolo, Gabriella; Araújo, Jaqueline de Paula; Lima, Joyce Alessandra; Brandt, João Victor [UNESP]; Bittencourt, João Vitor Silvano; Venturini, Ligia Milanez; Silveira, Paulo Cesar Lock; Rogers, Sylvia; Franzini, Cristina Maria; de Goes, Vivian Fernandes Furletti; Andrade, Thiago Antônio Moretti (Elsevier, 2021)
Objective: To evaluate formulations of 1 % silver (Ag) nanoparticles for treating traumatic lesions induced in the oral mucosa of rats, because these lesions are commonly observed in the dental clinic, and their therapeutic forms are scarce. Methods: Wistar rats were punch-injured (two circular fragments, 4.0 mm in diameter) in the oral mucosa (one on each side), and were treated topically (twice per week) with the treatments/groups including: no injury, control, vehicle, diluted Ag, soluble Ag, and solid Ag. On the 2nd, 7th, and 14th days postinjury, biopsies were collected for immunohistochemistry and biochemical analysis. Results: The group diluted Ag revealed a higher level of inflammatory infiltrate on the 2nd day, whereas solid Ag presented lower levels. The Ag solid group presented higher IL-1β on the 2nd day and increased IL-10 and TGF-β1 throughout the follow-up. Moreover, all three Ag groups presented lower levels of oxidative stress markers and, on the 7th day, the diluted Ag and solid Ag groups revealed higher antioxidants. Diluted Ag and soluble Ag groups presented greater blood vessels proliferation, whereas soluble Ag and solid Ag groups revealed greater VEGF on the 2nd and 14th days. Furthermore, all three Ag groups were highlighted during fibroplasia, although collagenesis was similar to that observed in the control group. Conclusions: Although diluted Ag was noticeable for its important angiogenesis and fibroplasia, solid Ag was the most suitable formulation in healing oral lesions as it efficiently controlled inflammation and oxidative stress, thus favoring angiogenesis and tissue formation.
Keywords: Angiogenesis; Antioxidant; Formulation; Inflammation; Oral wounds; Silver nanoparticle